USING “OMISSION” IN THE TRANSLATION PROCESS OF “THE HOUND OF THE BASKERVILLES” BY ARTHUR CONAN DOYLE. - Begaliyeva Marjona Normaxmatovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article is about using “omission” in the translation process of literary work and focuses on solving out translation problems.